Climate Change and Adaptation for the Region of the Santanderes: Perceptions and Considerations from the Legal Framework - Bedoya-Mashuth, Julia; Salazar de Cardona, Melva (DIXI, 2014)
Climate change has generated signifiant social, economic and environmental changes in the country, which has led to the recent formulation of national policies for adaptation, in addition to the activation and implementation of diverse regional actions. Ths article aims to respond to various questions relating to knowledge, activities, budgets, political will, impacts and other aspects associated with this phenomenon and, specifially, the possibilities for adaptation in the region of the Santanderes. Th research, through an empirical–analytical approach, examined such variables as climate change and adaptation and sought to determine and analyze the capacity for adaptation in that region. To do so, information sources from international, national and departmental entities were consulted and interviews were held with three focal groups along with implementation of a semi-structured online survey of offials and agencies in 127 municipalities.